Depressed Fracture of Calvarial Bone following Rapid Scalp Expansion for Post-burn Alopecia in a Child - P Kumar; K G Bhaskara; P C Thomas (Indian Journal of Plastic Surgery)
Depressed calvarial fracture as a complication of scalp expansion in a 3 1/2-year-old girl who underwent 8cm scalp expansion over 48 days is being reported. A technique for placement of tissue expander through multiple small radically placed incisions is described to prevent implant exposure.